Pengaruh Electronic Word Of Mouth (E-WOM) di Instagram Terhadap Keputusan Pembelian Pada Kangen Seblak Bojonegoro - Yolanda Dian Olivia; Muh Syarif (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this study was to determine the effect of Electronic Word Of Mouth (E-WOM) on purchasing decisions positively and significantly. The approach used in this study is a quantitative approach using survey methods. The sampling technique used in this study was purposive sampling, and analyzed using simple linear regression analysis. This study found that the value of